Comparison of Pin Tract Infection Rate in Buried Versus Unburid Krischner Wires Fixation in the Management of Gartland Type III Supracondylar Fracture of Humerus in Children (Journal of Pakistan Orthopaedic Association, 2024)
Objective: To evaluate the results of pin tract infection rate in buried versus unburied Kirshner wires fixation in the management of Gartland type III supracondylar fracture of humerus in children.Methods: This randomized control trials study was conducted in the Department of Orthopedics and Trauma, Medical Teaching Institute Lady Reading Hospital, Peshawar Pakistan from December 2020 to June 2021 on 62 (31 in each groups) patient having age range of less than 12 years of either gender having closed fracture of less than two days old with no neurovascular injury. All the patients were observed to compare pin tract infection rate in buried versus unburied Kirshner wires fixation in the management of Gartland type III supracondylar fracture of humerus in children. Sampling technique was non-probability consecutive sampling.Results: In this study age distribution among 62 patients was analyzed as n= 2 -4 Years 17(27.4%) 4-6 Years 14(22.6%) 6- 9 Years11(17.7%) 9-12 Years 20(32.3%). Mean age was 7.1 Years with SD ±2.87 (Gender wise Distribution among 62 Patients were analyzed as Male were 31(50.0%) and female were 31(50.0%) Distribution of duration of disease among 62 patients were analyzed as n= 1-2 weeks was 47(75.8%) and 3-4 weeks was 15(24.2%)BMI classification among 2 patients were analyzed as n= Below 18.5 Underweight was 25(40.3%) 18.5–24.9 Normal weight was 10(16.1%) 25.0–29.9 Pre-obesity was 17(27.4%) and 30.0–34.9 Obesity class was 9(14.5%)Distribution Pin tract Infection after 4 weeks among the groups were analyzed as n= Infection rate among Group A (K-Wires buried) was 4(12.9%) and Group B (K-Wires Unburied) 9(29.%)Conclusion: We believe that closed reduction and buried percutaneous lateral pinning is an efficient, reliable and safe method.